Awareness of stroke risk factors and warning signs in southern Brazil Avaliação de fatores de risco de doença cerebrovascular no sul do Brasil - Asdrubal Falavigna; Alisson Roberto Teles; Viviane Maria Vedana; Fabrício Diniz Kleber; Gabriela Mosena; Maíra Cristina Velho; Thaís Mazzocchin; Roberta Castilhos da Silva; Luzia Fernanda Lucena; Juliana Tosetto Santin; Felipe Roth (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the knowledge about stroke in Caxias do Sul. METHOD: A closed-ended, self-administered questionnaire was used to assess the knowledge about stroke among residents of Caxias do Sul. In order to verify variables associated to lack of knowledge we defined three main end points: (1) the inability to recognize that stroke is a disease that affects the brain; (2) insufficient knowledge of risk factors; (3) insufficient knowledge of signs and symptoms of acute stroke. RESULTS: A total of 952 subjects answered the questionnaire. Lower income and lower educational level were independent factors associated to inability to recognize that stroke affects the brain. Lower income and being under 50 years old were independent risk factors to lack of knowledge concerning stroke risk factors. Lower educational level was the unique risk factor for insufficient knowledge about stroke warning signs. CONCLUSION: There is a lack of knowledge about stroke in Caxias do Sul. People with lower socioeconomic status and lower education level should be the targets of educational campaigns. OBJETIVO: Avaliar o conhecimento sobre doença cerebrovascular em Caxias do Sul. MÉTODO: Um questionário auto-administrado, com questões objetivas, foi utilizado para avaliar o conhecimento sobre doença cerebrovascuar em residentes de Caxias do Sul. A fim de verificar as variáveis associadas à falta de conhecimento, definiram-se três principais desfechos: (1) incapacidade de reconhechecer que o derrame é uma doença que afeta o cérebro; (2) conchecimento insuficiente sobre fatores de risco; (3) conhecimeto insuficiente sobre sinais e sintomas de acidente vascular encefálico. RESULTADOS: Um total de 952 sujeitos responderam o questionário. Menor renda e menor nível socioeconômico foram fatores independentes associados à incapacidade de reconhecer que derrame afeta o cérebro. Menor renda e ter menos que 50 anos de idade foram fatores independentes associados à conchecimento insuficiente sobre fatores de risco para doença cerebrovasculas. Menor nível educacional foi o único fator de risco independente associado à conhecimento insuficiente sobre sinais de alerta do acidente vascular encefálico. CONCLUSÃO: Há uma lacuna de conhecimento sobre doença cerebrovascular em Caxias do Sul. Pessoas com menor nível socioeconômico e menor nível educaional deveriam ser o alvo para campanhas educacionais.